The Effect of Work-Based Learning and Experiential Learning Models on The Student’s Performance at Batam Welding Training Centre - Decky Antony Kifta; Muhammad Giatman; Wakhinuddin Simatupang; Ronal Watrianthos (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Global competition that are becoming increasingly intensive and this caused that learning models improvement are needed in various areas which includes the welding workshop training which educate the students to improve their welding skills and technique to comply with the industry requirements. The students’ performance is important factor which link the student’s ability to survive with the current work forces by implementing their expertise and the current condition of the industry. However, the learning models such as work based learning and experiential learning become very important role to achieve the students intended performance, therefore, after scrutiny research in the training premise, it appears that there is a hypothetical formula which led that work based and experiential learning models may have significant influence on the students’ performance. Work based learning and experiential learning are learning methods or models which bring the students to the condition and environment closer to the actual environment of workplace or the industry. Based on that hypothesis, a method of analysis was performed in this research and the linear regression analysis was used, and from the results it becomes apparent that work based learning and experiential learning models have positive impact and significant on the students’ performance.